The oribatid mite genus Nothrus Koch, 1836 (Acari: Oribatida: Nothridae) of South Africa, including a key to African species - Ermilov, Sergey G.; Hugo-Coetzee, Elizabeth A. (Zootaxa, 2012)
The oribatid mite genus Nothrus (Nothridae) is reported for the first time from South Africa, represented by Nothrus bi-longisetosus sp. nov., N. monolongisetosus sp. nov. and Nothrus anauniensis Canestrini & Fanzago. Nothrus bilongise-tosus sp. nov. is decribed base on adult, N. monolongisetosus sp. nov. is decribed base on all instars. Additional description of N. anuniensis is given. An identification key to all known African species of Nothrus is presented.